PENYULUHAN HUKUM TENTANG PENTINGNYA HAK KEKAYAAN INTELEKTUAL PADA KELOMPOK TENUN TRADISIONAL “BIA BEREK” DI DESA KUNERU – ATAMBUA (NTT) - Valerie Selvie Sinaga (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
Intellectual Property Rights (IPR) is a set of rights granted to exploit an object that is the result of human thought. IPR consists of various rights including copyright, trademark, patent, industrial design, and trade secrets. These rights are needed in developing a business, both large and small businesses. Legal counselling on the importance of IPR was given to the